Demystifying Internet-Wide Service Discovery - Leonard, Derek; Loguinov, Dmitri (IEEE/ACM transactions on networking, 2013)
This paper develops a high-performance, Internet-wide service discovery tool, which we call IRLscanner, whose main design objectives have been to maximize politeness at remote networks, allow scanning rates that achieve coverage of the Internet in minutes/hours (rather than weeks/months), and significantly reduce administrator complaints. Using IRLscanner and 24-h scans, we perform 21 Internet-wide experiments using six different protocols (i.e., DNS, HTTP, SMTP, EPMAP, ICMP, and UDP ECHO), demonstrate the usefulness of ACK scans in detecting live hosts behind stateless firewalls, and undertake the first Internet-wide OS fingerprinting. In addition, we analyze the feedback generated (e.g., complaints, IDS alarms) and suggest novel approaches for reducing the amount of blowback during similar studies, which should enable researchers to collect valuable experimental data in the future with significantly fewer hurdles.